High-fidelity simulation for mental health nurse residents: a mixed-methods study of communication competencies and learning perceptions - González Luis, Julio; Sánchez Adsuara, Jesús; Medrano Andrés, Almudena; Corral Liria, Inmaculada; Losa Iglesias, Marta; Alonso Maza, Miriam (Frontiers in Medicine, 2025)
BackgroundHigh-fidelity clinical simulation is increasingly used in postgraduate nursing education, particularly in mental health training, where it can support the acquisition of competencies for managing complex situations such as suicidal behavior.ObjectiveTo explore the perceptions and learning outcomes of mental health nursing residents during high-fidelity simulation sessions, with a focus on communication, affective context, and professional competencies.MethodsA mixed study was conducted with a qualitative core design and a complementary quantitative component. Sixty-nine first- and second-year mental health nursing residents from the Community of Madrid participated in simulation sessions structured according to the MAES© methodology. Qualitative data (focus groups, written reports, field notes) were analyzed thematically by three independent researchers, ensuring rigor through triangulation, member checking, and reflexivity. Quantitative contextual data were obtained through a checklist of nursing interventions and descriptive statistics.ResultsThe analysis generated three overarching themes: Communication style (residents emphasized active listening and the importance of non-verbal language; e.g., “Sometimes silence says more than words”), Affective context (awareness of their own emotional impact during patient interactions), and Training, knowledge, and experience (residents identified gaps and valued simulation as a safe environment to bridge them). Quantitative results supported these findings but were interpreted only as contextual information.ConclusionsHigh-fidelity simulation promotes the integration of theoretical knowledge into practice, strengthens self-confidence, and contributes to safer management of suicidal behavior in clinical contexts. The findings support the transferability of simulation-based training to mental health practice and highlight the need for longitudinal research to evaluate its impact on real patient outcomes.